Control of quarter electric vehicle based on PACEJKA tire model by fuzzy sliding controller - Baz, Rachida; El Majdoub, Khalid; Giri, Fouad; Ammari, Ossama (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper presents the design of a hybrid intelligent fuzzy sliding controller (HIFSC) for a purely electric quarter vehicle (QEV) using a brushless DC (BLDC) motor and a PACEJKA tire model. The proposed system processes control signals to manage the QEV's dynamic longitudinal behavior. The BLDC motor and tire are modeled together to form an in-wheel motor system, which is inherently non-linear and subject to uncertainties. To address these challenges, an intelligent controller integrating sliding mode control (SMC) with fuzzy logic tuning is proposed. While SMC is effective in managing non-linearities, it is prone to chattering. The incorporation of fuzzy logic aims to mitigate this issue, ensuring stability and maintaining the sliding mode. The system and controller were simulated using MATLAB/Simulink. Simulation results demonstrate that the fuzzy sliding mode controller outperforms the conventional PI controller by reducing chattering and enhancing the system's sensitivity to external noise, without overshooting across various road conditions. Notably, the slip rate achieves a maximum of around 2.1% on wet roads.